Does Natural Killer Cell Deficiency (NKD) Increase the Risk of Cancer? NKD May Increase the Risk of Some Virus Induced Cancer - Moon, Won Young; Powis, Simon J. (Frontiers in Immunology, 2019)
Natural killer cell deficiency (NKD) is a primary immunodeficiency where the main defect lies in CD56+CD3- natural killer (NK) cells which mediate cytotoxicity against tumours. Most cases are observed in children and adolescents with recurrent viral infections and cancer. GATA2 and MCM4 mutations are found in NKD patients with cancer. However, the question remains unclear whether NKD increases the risk of cancer. Mutations in the second zinc finger of GATA2 cause both NKD and haematopoietic malignancies. MCM4 splice site mutations are found in NKD patients and they increase susceptibility to DNA instability during replication. IRF8, RTEL1, and FCGR3A mutations are associated with NKD but their associations with cancer are unknown. Based on the studies, it is hypothesised that genetic mutations alone are sufficient to cause cancer. However, a number of NKD patients developed oncogenic viral infections which progressed into cancer. Here, we review the evidence of genetic mutations responsible for both NKD and cancer to identify whether NKD contributes to development of cancer. The findings provide insights into the role of NK cells in the prevention of cancer and the significance of assessing NK cell functions in susceptible individuals.